THE EFFECTS OF ONLINE TEACHING AND LEARNING ON LECTURERS DURING CORONAVIRUS DISEASE-2019 AT THE UNIVERSITY OF LIMPOPO, SOUTH AFRICA - Rivoningo Nyiko Msisinyane; Prof Witness Maluleke (CV. RADJA PUBLIKA, 2025)
This paper aims to explore the effects of online teaching and learning (T & L) on lecturers during Coronavirus-Disease-2019 at the University of Limpopo (UL) within the Department of Criminology and Criminal Justice. This study adopted a qualitative research approach, employing an exploratory research design. Non-probability purposive sampling was deployed. To collect data in this study, the researchers employed semi-structured Key Informant Interviews (KIIs). The semi-structured interview schedule, created using Google Forms, was emailed to the Ten (10) lecturers who provided their email addresses indicating their willingness to participate in the interview. The findings of this study presented significant negative effects that were encountered by lecturers in the shift to online T & L, including declines in student attendance, engagement, and participation. These issues were primarily due to technical difficulties such as internet connectivity problems, power outages, and the lack of provision of electronic devices. However, the university took proactive measures to lessen the impact of these issues, including providing electronic devices and data bundles, enhancing technology infrastructure, and offering workshop training. The researchers recommend the university to improve internet connectivity, provide ongoing support for lecturers and students, ensure access to necessary equipment, and make financial commitments toward improving digital facilities.